Kajian Sosiolinguistik terhadap Persepsi Kekasaran dalam Gaya Berbicara Masyarakat Makassar - Andi Nurrahmi Azani Alwi; Arief Fiddienika; Dyah Adila Perdana (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
This research examines the perception of roughness in the speaking style of the Makassar community through a sociolinguistic approach. The distinctive speaking style of the Makassar community, characterized by high intonation, assertive tone, and the use of address terms such as "ji" and "ko," is often perceived differently by people from outside the region. Using a qualitative method with an online survey of 15 respondents from various regions in Indonesia, this research reveals that perceptions of roughness are more influenced by intonation and tone of voice rather than word choice. The findings indicate that cultural background, interaction experience, and communication context play significant roles in shaping one's perception of the Makassar community's speaking style. Respondents from regions with similar linguistic characteristics or those who have long interacted with the Makassar community tend not to view this speaking style as a form of roughness, but rather as an expression of cultural identity. The research results also reveal generational variations, where younger generations are perceived as using a "rougher" speaking style compared to older generations. The Makassar community itself views their speaking style as part of their cultural identity, not a form of roughness, and shows resistance to negative stereotypes. This research contributes to the development of sociolinguistic theory concerning the relationship between language, identity, and linguistic stereotypes, as well as provides practical implications for language education and intercultural communication in Indonesia's multicultural context. These findings emphasize the importance of a cultural relativism approach in understanding language variation, where the assessment of a linguistic practice must consider the norms and values prevailing in the community.